The Asymptotic Solution of the Initial Boundary Value Problem to a Generalized Boussinesq Equation - Zheng Yin; Feng Zhang (Abstract and Applied Analysis)
The L2 space solution of an initial boundary problem for a generalized damped Boussinesq equation is constructed. Certain assumptions on the coefficients of the equation are found to show the existence and uniqueness of the global solution to the initial boundary problem. The explicit expression for the large time asymptotic solution is obtained.